Extremos de umidade na América do Sul e a contribuição do Oceano Atlântico Sul - Scricco, Iara Mineiro (2016)
Extreme climatic events have been occurring with greater intensity and/or frequency over South America. Indicatives for these alterations encompass natural climate variability, land use (deforestation and urbanization), global warming, and increase of greenhouse gases and aerosols in the atmosphere. South America receives a great input of moisture from the Amazon rainforest, as well as a 37% contribution from the Atlantic Ocean. Considering the whole planet, some atmospheric events need to be analyzed when regarding moisture input towards a continent. Ocean circulation can interfere for example in sea surface temperature (SST), either influencing or not the input of moisture to the continent. The objective of the present study was to analyze the variability of atmospheric moisture in South America and its extreme values, as well as the relationships with the sea surface temperature of the adjacent oceans. The present study made use of ECMWF data, ERA-INTERIM reanalysis (pressure at sea level and surface pressure, evaporation, air and dew point temperatures at 2 meters, and zonal and meridional wind at 10 meters) and also sea surface temperature data from the MetOffice Hadley Centre (HADISST). The analysis period of the present study was between 1980 and 2009, encompassing a period of 30 years of data. First, climatology, trends and extremes of moisture and evaporation (frequency, intensity and reoccurrence of events) were calculated. These were followed by lagged compositions to assess the role of sea surface temperature anomalies during extreme moisture and evaporation events. The main results found were regarding an increase of the pressure at sea level gradient and SST in the southwestern Atlantic, increase evaporation in the eastern and northern coasts of South America, and its decrease in the center-southern region of the continent. Moreover, the center-southern region also demonstrated a decrease of dew point temperature and specific moisture, and an increase in the difference between air temperature and dew point temperature. Decrease in the moisture flow magnitude and intensification of dry events over the center-southern region of South America were also observed. Finally, results showed that an SST anomaly cycle during an extreme event in the continent lasted approximately five months and, at least one month prior to the event, signs of this SST anomaly were already observable. In summary, the most significant moisture alterations in South America were found in the center-southern sector of the continent and over the southwestern Atlantic Ocean, near the Brazil-Malvinas Confluence (BMC). Nevertheless, more studies are needed to understand the relationships between SST at the BMC and moisture extremes, particularly in the center-southern portion of South America.